The immune checkpoint CD96 defines a distinct lymphocyte phenotype and is highly expressed on tumor‐infiltrating T cells. Issue 2 (17th October 2018) - Lepletier, Ailin; Lutzky, Viviana P; Mittal, Deepak; Stannard, Kimberley; Watkins, Thomas S; Ratnatunga, Champa N; Smith, Corey; McGuire, Helen M; Kemp, Roslyn A; Mukhopadhyay, Pamela; Waddell, Nicola; Smyth, Mark J; et al.
Abstract: CD96 has recently been shown to be a potent immune checkpoint molecule in mice, but a similar role in humans is not known. In this study, we provide a detailed map of CD96 expression across human lymphocyte lineages, the kinetics of CD96 regulation on T‐cell activation and co‐expression with other conventional and emerging immune checkpoint molecules. We show that CD96 is predominantly expressed by T cells and has a unique lymphocyte expression profile. CD96 high T cells exhibited distinct effector functions on activation. Of note, CD96 expression was highly correlated with T‐cell markers in primary and metastatic human tumors and was elevated on antigen‐experienced T cells and tumor‐infiltrating lymphocytes. Collectively, these data demonstrate that CD96 may be a promising immune checkpoint to enhance T‐cell function against human cancer and infectious disease. Abstract : CD96 has recently been shown to be a potent immune checkpoint molecule in mice, but a similar role in humans is not known. In this study, we show that CD96 is predominantly expressed by T cells and has a unique lymphocyte expression profile. CD96 expression was elevated on antigen‐experienced T cells and tumor‐infiltrating lymphocytes.